2021
DOI: 10.1038/s41467-021-25715-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic requirements of NK cells during the acute response against retroviral infection

Abstract: Natural killer (NK) cells are important early responders against viral infections. Changes in metabolism are crucial to fuel NK cell responses, and altered metabolism is linked to NK cell dysfunction in obesity and cancer. However, very little is known about the metabolic requirements of NK cells during acute retroviral infection and their importance for antiviral immunity. Here, using the Friend retrovirus mouse model, we show that following infection NK cells increase nutrient uptake, including amino acids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 65 publications
(116 reference statements)
4
26
0
Order By: Relevance
“…Moreover, systematic low iron level influenced by hepcidin resulted in the suppression of NK cell activation and production of IFN-γ. Besides, they also showed that sufficient serum iron is critical to the metabolism of NK cells and their activity against virus infection ( 46 ). Accordingly, iron plays a pivotal role not only in the development and proliferation but also in the activation and function of NK cells when virus infection occurred.…”
Section: Iron and Nk Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, systematic low iron level influenced by hepcidin resulted in the suppression of NK cell activation and production of IFN-γ. Besides, they also showed that sufficient serum iron is critical to the metabolism of NK cells and their activity against virus infection ( 46 ). Accordingly, iron plays a pivotal role not only in the development and proliferation but also in the activation and function of NK cells when virus infection occurred.…”
Section: Iron and Nk Cellsmentioning
confidence: 99%
“…Cytokines such as interferon (IFN)-γ and tumor necrosis factor (TNF) produced by NK cells not only activate immune response but also make NK cells become sensitive to other cytokines (e.g., interleukin-2, IL-12, IL-15 and IL-18) ( 42 , 43 ). Activated NK cells increase expression of transferrin receptor (CD71) ( 44 , 45 ), whereas iron deficiency results in a lose function of NK cells ( 46 ). All of these indicate that iron is indispensable in the activation of NK cells.…”
Section: Iron and Nk Cellsmentioning
confidence: 99%
“…Neutrophils, monocytes/macrophages ( 246 , 247 ) and NK cells ( 248 ) use iron to combat pathogens. During intracellular infection, they release iron-loaded lactoferrin into their phagocytic vacuoles where ferrous iron functions as a catalyst of the Haber-Weiss reaction, generating reactive oxygen species (ROS) ( 249 ).…”
Section: Immune Cells Under Iron-deficient Conditionsmentioning
confidence: 99%
“…Hepcidin blocks iron recycling by hemophagocytic macrophages and iron absorption by duodenal enterocytes, suppressing serum iron concentrations (4). This response can protect against certain siderophilic bacterial pathogens, constituting an acute "nutritional immune" mechanism but, if prolonged, leads to inflammatory anemia and can inhibit proliferative lymphocyte responses to immunization and infection (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%